Revealing the association between vitamin D metabolic pathway gene variants and lung cancer risk: a systematic review and meta-analysis - Elsalahaty, Mohamed I.; Alkafaas, Samar Sami; Bashir, Aya O.; El-Tarabily, Khaled A.; El-Saadony, Mohamed T.; Yousef, Eman H. (Frontiers in Genetics, 2024)
Lung cancer is a crucial global issue, with more than one million deaths annually. While smoking is considered the main etiology of the disease, several genetic variants are associated with it. Alterations in vitamin D pathway genes have also been studied in regards to lung cancer, but the findings have been inconclusive. We here present a systematic review and meta-analysis of seven genes in this pathway: CYP2R1, CYP27B1, CYP24A1, CYP3A4, CYP3A5, GC, and VDR. Four databases (PubMed, Scopus, Cochrane Library, and Web of Science (WOS) databases) were searched. From these, 16 eligible case–control studies comprising 6,206 lung cancer cases and 7,272 health controls were obtained. These studies were subjected to comprehensive data extraction and quality scoring, and the pooled odds ratio with a 95% confidence interval was calculated to estimate the effect of each variant along with heterogeneity analysis and a risk of bias assessment. Our meta-analysis revealed an association between CYP3A4 (rs2740574) and lung cancer in the allelic, heterozygous, and dominant models. In addition, both VDR (Fok1: rs2228570) and VDR (Cdx-2: rs11568820) displayed a protective role in lung cancer development in the heterozygous and dominant models. Furthermore, VDR (Taq1: rs731236) showed a decreased risk of lung cancer in the allelic, homozygous, and recessive models. Similarly, VDR (BsmI: rs1544410) had a positive effect on lung cancer risk when subjected to allelic and recessive models. Our meta-analysis revealed the lack of association of CYP2R1 (rs10741657), CYP27B1 (rs3782130), CYP27B1 (rs10877012), CYP24A1 (rs6068816), CYP24A1 (rs4809960), CYP3A5 (rs776746), GC (rs7041), GC (rs4588), and VDR (ApaI: rs7975232) with lung cancer. Our work revealed that CYP3A4 (rs2740574) can represent an independent risk factor for lung cancer. This conclusion can aid better personalized medicine for lung cancer management, while further assessment for genetic variants of CYP3A4, CYP27B1, CYP24A1, GC, and VDR is still required to address more robust evidence.